ANALISIS EFEKTIVITAS PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN CIMANGGIS, KOTA DEPOK - Munir Saputra; Ahmad Hidayat Rahadian (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2018)
This research was conducted to determine the effectiveness of policies for integrated administrative service/ PATEN in District Town Cimanggis, Depok City.  Research using qualitative methods to describe and analyze the objective. The results showed that the effectiveness has not met the minimum standards, but in general the community felt a change was quite good with one-stop service.Several things that make service ineffective namely the unavailability of the service manual , the fees charged , the suggestion box as an evaluation , an online registration facility , which has not been scheduled service personnel and their dependence on the head section that is hindering the speed of service.Some efforts have been made to improve the effectiveness is improving the competence of personnel , implementing e - PATEN and the need for city government's commitment to improve the efficiency and effectiveness of the implementation PATEN in District CimanggisThis research was conducted to determine the effectiveness of policies for integrated administrative service/ PATEN in District Town Cimanggis, Depok City.  Research using qualitative methods to describe and analyze the objective. The results showed that the effectiveness has not met the minimum standards, but in general the community felt a change was quite good with one-stop service.Several things that make service ineffective namely the unavailability of the service manual , the fees charged , the suggestion box as an evaluation , an online registration facility , which has not been scheduled service personnel and their dependence on the head section that is hindering the speed of service.Some efforts have been made to improve the effectiveness is improving the competence of personnel , implementing e - PATEN and the need for city government's commitment to improve the efficiency and effectiveness of the implementation PATEN in District Cimanggis